Advanced Trauma and Surgery - Fu, Xiaobing; Liu, Liangming (Springer Singapore : Imprint: Springer, 2017)
This book discusses different aspects of trauma surgery, ranging from the various types of trauma and their management, infection, sepsis and inflammation to tissue injury and repair in trauma. It discusses cellular, molecular and genetic research findings and their role in pathogenesis in trauma and injury. In addition, it highlights the translational application of advanced theories and technologies in the management of trauma patients. This book is a valuable resource for anyone involved in the management of severe trauma damage to tissues wanting to reduce early mortality and improve patients' quality of life. Editor Xiaobing Fu is a professor and director of the Key Laboratory of Wound Repair and Regenerative Medicine of PLA, The First Affiliated Hospital of the PLA General Hospital, Beijing, China. Professor Fu is also an academician of Chinese Academy Engineering. Editor Liangming Liu is a professor at the State Key Laboratory of Trauma, Burns, and Combined Injury, Daping Hospital, Third Military Medical University, Chongqing, China.
Keywords: Medicine.; Traumatology.; elektronické knihy; electronic books